Exploring the experiences of residents and their families in an alcohol-related brain injury residential rehabilitation unit in Northern Ireland: a qualitative study - Campbell, Anne; Millen, Sharon; Jordan, Uisce; Watson, Diane; Watson, Joy; McCorry, Roger (Frontiers in Public Health, 2024)
Brain Injury (ARBI). Exploring the impact of a rehabilitation service on individuals with ARBI and their relatives/caregivers, this study aimed to gain insights into their experiences and assess how the service influenced cognitive functioning, psychological well-being, social relationships, community engagement, and the desire for abstinence.This was a qQualitative, semi structured interview study as part of a larger mixed methods study of with resident andresidents and their family members. Data was collected over 4 timepoints with n= 20 residents: baseline (n=20 interviews), 6 months (n=15 interviews), 12 months (n=6 interviews ) and at discharge (n=8 interviews ). The interviews took place at a specialist residential rehabilitation facility for people with ARBI.. Remote interviews were conducted with family members (n=10). A thematic analysis of transcripts using NVivo software was undertaken.Qualitative findings for residents with ARBI across 4 timepoints from baseline to time of discharge indicated an improvement in all outcomes. Overall, residents reported that the ARBI holistic intervention significantly improved psychological wellbeing, social relationships/community participation, functioning abilities, and abstinence from alcohol, particularly when residents were residing in the unit. Family members and carers presented more trepidation regarding the long-term impacts.Whilst the residential unit provided structure and a protective environment, residents required ongoing support post discharge for their addictive behaviours. An outreach intervention for these individuals is currently being piloted.